What drives university applications? An attempt to explain aggregate demand for higher education - Vieira, Carlos (2014)
Low educational attainment is frequently pointed out as a barrier to social and economic development and most governments aim at increasing participation in higher education. However, effective strategies to increase aggregate demand require information on its most relevant determinants, which is difficult to obtain because applications to higher education are usually not organised at the country level. In this study, we utilise a large sample of data on applications available in Portugal to estimate a model of aggregate demand for higher education. Our estimates suggest that the economic context is relatively less relevant than policy orientations, and thus that sustaining or increasing higher education participation may be more dependent on political choice than on economic circumstances. The only relevant economic determinant in the model is unemployment which contradicting some previous research appears to exert a negative impact upon aggregate demand.